Academic Supervision of The Head of Madrasah in Indonesia: A Meta-Analysis - AH Sahaludin; Wawan Wahyudin; Agus Gunawan (IJGIE (International Journal of Graduate of Islamic Education), 2023)
One of the efforts to improve teacher performance can be made by applying academic supervision. This article aims to analyze the academic supervision of madrasa principals in Indonesia. A meta-analysis is used as a research method. A total of 20 nationally accredited journals were selected to be the journals analyzed. Through the search column, 51 articles related to academic supervision were found. These data are collected, categorized, displayed, and concluded. The results of the analysis found that madrasah heads need to determine the right strategy to overcome the problem of teacher professionalism through academic supervision. Academic supervision activities are a series of activities carried out by the head of the madrasah to help teachers explore and develop their competencies to manage learning activities properly.